Hours vs employment in response to demand shocks - Robert A. Hart (IZA World of Labor, 2017)
Labor market responses to temporary aggregate demand shocks are commonly analyzed and discussed in terms of changes in employment and unemployment. However, it can be seriously misleading to ignore the interrelated behavior of hours worked.Work hours can be altered relatively speedily and flexibly, and this strongly relates to employment, labor productivity, and unemployment outcomes. The hours–employment distinction is especially important in the evaluation of the performances of European labor marketsduring the negative shock experienced during the Great Recession.
Keywords: E24; E32; J23; 330; demand shocks; hours; employment; labor productivity